Book Review: Familias e infancias en la historia contemporánea: Jerarquías de clase, género y edad en Argentina [Families and Childhoods in Contemporary History: Class, Gender and Age Hierarchies in Argentina], by Isabella Cosse (Ed.) - Silva Balerio, Diego (Revista de historia., 2023)
Research on childhood, adolescence, and family in Latin America has a longstanding tradition and, at the same time, an arduous task that lies ahead. The book under review is the result of a collaborative project that studies 20th-century social hierarchies in Argentina from the perspective of childhood and the family. Its authors are researchers with a solid background in history. These researchers conduct their work within the framework of the Historical Research Group on Families and Childhood in Contemporary Argentina, based at the Interdisciplinary Institute of Gender Studies within the Faculty of Philosophy and Letters at the University of Buenos Aires.